2017
DOI: 10.1590/0001-3765201720160892
|View full text |Cite
|
Sign up to set email alerts
|

Richness and structure of ant assemblies (Hymenoptera: Formicidae) in Atlantic forest in southern Brazil

Abstract: Ant diversity is influenced by the structural complexity of the environment. Ants are thus an ecologically important group due to their potential to serve as indicators of environmental quality. The objective of this study was to evaluate ant diversity in areas with different land use histories and thus, within different stages of regeneration in the Permanent Preservation Area of the Foz do Chapecó Hydroelectric Plant reservoir. Ant assemblies among sample sites were compared using rarefaction analysis, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…Species that exist in litter, bush, and terrain locations in the Serdang Menang Village plantation are certainly more than ant species that are interested in coconut oil. It can be assessed that on ant inventory in other regions as conducted by Lutinski et al (2017), found 52 species of ants in the Atlantic forest, South Brazil. Ranny et al (2015), found 12 species of ants in the Lubuk Minturun dragon fruit plantation.…”
Section: Resultsmentioning
confidence: 99%
“…Species that exist in litter, bush, and terrain locations in the Serdang Menang Village plantation are certainly more than ant species that are interested in coconut oil. It can be assessed that on ant inventory in other regions as conducted by Lutinski et al (2017), found 52 species of ants in the Atlantic forest, South Brazil. Ranny et al (2015), found 12 species of ants in the Lubuk Minturun dragon fruit plantation.…”
Section: Resultsmentioning
confidence: 99%
“…Ants of the genus Solenopsis are associated with anthropization (Lutinski et al 2014(Lutinski et al , 2017b, loss and fragmentation of tropical forests, reducing the richness of other ant species by competitiveness (Dejean et al 2015). This is the case of Solenopsis saevissima, a species that is often found in environments modified by man.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the rarefaction curves, they did not reach asymptote, indicating that the sampling effort did not fully analyze the ant assemblies, being possible to register additional species in all environments. However, the lack of stabilization in the sampling curves is commonly observed in ant communities, a pattern that may be related to the aggregate distribution or rarity of some species (Lutinski et al 2017b(Lutinski et al , 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Terdapat sekurang-kurangnya dua generasi semut pekerja bagi memastikan koloni sentiasa stabil (Collingwood et al 2011). Sifat ini telah menjadikan semut sebagai haiwan majoriti di dalam sesuatu habitat contohnya ladang kelapa sawit (Lutinski et al 2017). Justeru, ini menjadikannya calon yang sesuai sebagai penunjuk biologi ekosistem dan sekaligus menekankan kepentingan kajian ekologi kumpulan serangga tersebut.…”
Section: Pengenalanunclassified